The NSD family of protein methyltransferases in human cancer. (August 2015) - Vougiouklakis, Theodore; Hamamoto, Ryuji; Nakamura, Yusuke; Saloura, Vassiliki
The NSD family of protein lysine methyltransferases consists of NSD1, NSD2/WHSC1/MMSET and NSD3/WHSC1L1. NSD2 haploinsufficiency causes Wolf-Hirschhorn syndrome, while NSD1 mutations lead to the Sotos syndrome. Recently, a number of studies showed that the NSD methyltransferases were overexpressed, amplified or somatically mutated in multiple types of cancer, suggesting their critical role in cancer. These enzymes methylate specific lysine residues on histone tails and their dysfunction results in epigenomic aberrations which play a fundamental role in oncogenesis. Furthermore, NSD1 was also reported to methylate a nonhistone protein substrate, RELA/p65 subunit of NF-κB, implying its regulatory function through nonhistone methylation pathways. In this review, we summarize the current research regarding the role of the NSD family proteins in cancer and underline their potential as targets for novel cancer therapeutics.